EFL Students Perception of MALL for Pronunciation Proficiency - Aulia, Defani Fitridona; Indrayadi, Toni (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
Mobile Assisted Language Learning (MALL) greatly influences the success of pronunciation proficiency. Several previous studies have been conducted on the positive effect of MALL on Increasing pronunciation proficiency. however, the students' perceptions of MALL in increasing pronunciation proficiency are rare. Therefore, it is necessary to investigate the perception of using the teaching technological tool. This study used a survey research design. Sixty-nine English students at one Islamic higher education institution in Jambi, Indonesia voluntarily participated in this study. Data from participants were collected using questionnaires and then analyzed using SPSS 26. The research results showed that there was a statistically significant difference in perception of the usefulness of MALL, but no statistically significant difference in perception of the ease of MALL regarding gender. This means that the results indicated that the students positively perceive MALL in the process of teaching and learning.